Catalytic Hydrogenations with Cationic Heteroleptic Copper(I)/N-Heterocyclic Carbene Complexes - Thiel, Niklas O.; Brechmann, Lea T.; Teichert, Johannes F. (Synlett, 2019)
A new heteroleptic cationic copper(I) complex bearing two N-heterocyclic carbene (NHC) ligands has been prepared. In situ, a Cu–O bond can be generated which enables the complex to catalytically activate H2. The resulting complex shows activity in catalytic chemo- and stereoselective alkyne semihydrogenations as well as conjugate reductions of enones.
Keywords: copper; NHC ligands; hydrogenation; homogeneous catalysis; alkynes; enones